PENGARUH JUMLAH KENDARAAN BERMOTOR DAN KENDARAAN TIDAK MELAKUKAN DAFTAR ULANG TERHADAP PENERIMAAN PAJAK KENDARAAN BERMOTOR (Jurnal Proaksi, 2022)
AbstractMotor vehicle tax revenue is very important in increasing provincial taxes and can be used as a support for high provincial revenues, with increasing motor vehicle tax revenues can encourage the development of regional infrastructure. The purpose of this study was to test the effect of the number of motor vehicles and non-re-registering vehicles on motor vehicle tax revenues. The data used in this study is secondary data using the time series for the 2017-2021 period. The sample used in this study used monthly data from 2017-2021, so as to get 60 samples. The sample technique used is universal sampling. This research used a documentation method conducted at the Kantor Pusat Pengelolaan Pendapatan Kabupaten Cirebon 1 Sumber. The data analysis used in this study was multiple linear regression analysis. The results of this study partially show that the number of vehicles has a positive influence on motor vehicle tax revenues, and vehicles not re-registering have no effect on motor vehicle tax revenues, while simultaneously the number of motor vehicles and vehicles not re-registering has a positive effect on motor vehicle tax revenues.Keywords: Vehicle Tax, Motor Vehicle, Local Tax